New Social Risks Affecting Children. A Survey of Risk Determinants and Child Outcomes in the EU - Rainer Eppel; Thomas Leoni (Austrian Institute of Economic Research (WIFO), 2011)
Socio-economic transformations associated with the shift to post-industrial societies have not only created new opportunities and prosperity, but have also given rise to the emergence of new social risks occurring at different stages of life. This paper examines the situation of children, who can arguably be considered a particularly vulnerable social group. It provides an overview of the changes generating child-related risk structures and, given this background, compares child well-being outcomes across a number of dimensions in the countries of the EU 15. The analysis reveals considerable heterogeneity both across and within welfare state regimes, suggesting overall a sort of "North-South-divide" with Nordic Europe coming out on top and Southern Europe on the bottom. In Austria, children seem to be better-protected from poverty risk than the average child in the EU 15. However, the level of material well-being is lower compared to the Nordic countries and does not translate into equally good performance in all the selected non-material domains.
Keywords: 330; Kinder; Soziale Lage; Risiko; Sozialstaat; Systemvergleich; EU-Staaten